STUDENTS’ PERCEPTIONS ON USING YOUTUBE AS MEDIUM IN LEARNING SPEAKING SKILLS AT ENGLISH DEPARTEMENT UIN MATARAM IN ACADEMIC YAER 2023/2024 - Rita sonia (Journal of English Education and Literature, 2024)
This research is about students' perceptions on using YouTube in learning speaking skills independently at English department of UIN Mataram. The aims of the research are (1) To find out the perceptions of English major students who learning speaking via YouTube, (2) To find out the type of content used in learns speaking via YouTube. This type of research is quantitative and qualitative research. The subjects of this research were the first and seventh semesters of the English Language Education Study Program at UIN Mataram. The data collection techniques are questionnaires and interviews. Data collection takes the form of data reduction, data presentation, and drawing conclusions/verification and triangulation methods to ensure data trustworthiness. The results of research on students' perceptions of using YouTube to learn to speak in independent learning in the English Education Study Program are that students learn English from YouTube through music, films, Dialogue videos, and speech. And the results show that most of them use music to learn to speak because the songs are easy to memorize, especially songs that are trending among them, they can easily remember the vocabulary in the song's lyrics. Students responded positively about using YouTube as a learning medium. However, they also found difficulties when learning to speak from YouTube. They don't know what they're doing if they make a mistake because they learn independently.